2022
DOI: 10.3389/fgene.2022.894844
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Analysis of StTGA Genes Reveals the Critical Role in Enhanced Bacterial Wilt Tolerance in Potato During Ralstonia solanacearum Infection

Abstract: TGA is one of the members of TGACG sequence-specific binding protein family, which plays a crucial role in the regulated course of hormone synthesis as a stress-responsive transcription factor (TF). Little is known, however, about its implication in response to bacterial wilt disease in potato (Solanum tuberosum) caused by Ralstonia solanacearum. Here, we performed an in silico identification and analysis of the members of the TGA family based on the whole genome data of potato. In total, 42 StTGAs were predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Previous reports also indicated that interactions between SVP and FLM isoforms modulated the temperature-responsive induction of flowering in Arabidopsis [51]. StTGAs were generally expressed in different tissues at different stages of development [52]. At WRKY70 was involved in drought response [53], and IbNAC3 modulates combined salt and drought stresses [54], while the expression level of TaWRKY70 was increased significantly when exposed to high temperature.…”
Section: Discussionmentioning
confidence: 91%
“…Previous reports also indicated that interactions between SVP and FLM isoforms modulated the temperature-responsive induction of flowering in Arabidopsis [51]. StTGAs were generally expressed in different tissues at different stages of development [52]. At WRKY70 was involved in drought response [53], and IbNAC3 modulates combined salt and drought stresses [54], while the expression level of TaWRKY70 was increased significantly when exposed to high temperature.…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, in Solanum lycopersicum, brassinoidsteroid (BR) induces the expression of TGA2, which in turn triggers the removal of pesticide residues in tomatoes by inducing apoplastic ROS [13]. The TGA factors have been associated with enhanced resistance to biotic stressors in various plant species; for instance, the StTGA gene has been linked to the improved ability to withstand bacterial wilt in Solanum tuberosum (potato) [14]. GmTGAs have been reported to improve symbiotic nodulation and nitrogen use efficiency in Glycine max (soybean) [15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to functional roles in stress response pathways, TGA1 and TGA4 have been recognized as important regulatory factors of the nitrate response in Arabidopsis roots, exemplifying the versatility of these factors in nutrient signaling and utilization [17]. Currently, the TGA gene family has been identified and functionally analyzed in soybeans [1], peanuts [18], and potatoes [14], where 27, 20, and 42 TGA genes have been identified, respectively. The ongoing elucidation of TGA gene functions continues to reveal new aspects of their contribution to plant resilience and offers promising targets for crop improvement strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, comprehensive analyses of the TGA transcription factor have been reported in soybean [18], potato [19], tomato [20,21], and peach [22]. The TGA enhances the plant's resistance to the pathogen in tomato and peach.…”
Section: Introductionmentioning
confidence: 99%